1999
DOI: 10.1002/1529-0131(199905)42:5<1051::aid-anr26>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-? may exacerbate cryoglobulinemia-related ischemic manifestations: An adverse effect potentially related to its anti-angiogenic activity

Abstract: The discovery of the strong association between hepatitis C virus (HCV) infection and the development of mixed cryoglobulinemia has motivated active testing of antiviral-directed alternative therapies. Several trials have demonstrated that classic cryoglobulinemia-associated manifestations improve with interferon-alpha (IFNalpha) treatment. Herein we report on 3 HCV-infected patients with severe cryoglobulinemia-related ischemic manifestations who were closely followed up during IFNalpha therapy. Clinical eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 15 publications
(25 reference statements)
1
16
0
1
Order By: Relevance
“…According to this hypothesis, we have previously shown that angiogenesis inhibition with interferon ␣ may have devastating effects on ischemic lesions from patients with hepatitis C virus-related cryoglobulinemic vasculitis. 18 Using in vitro and in vivo models, we showed that a strong angiogenic response in temporal artery samples and strong angiogenic activity in serum are associated with a reduced prevalence of ischemic complications in patients with GCA, supporting the concept that the angiogenic response has a significant compensatory role in this disease. The angiogenic response in temporal arteries may not be functionally relevant in compensating for ischemia, but neovascularization may be crucial at distal sites in target organs.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…According to this hypothesis, we have previously shown that angiogenesis inhibition with interferon ␣ may have devastating effects on ischemic lesions from patients with hepatitis C virus-related cryoglobulinemic vasculitis. 18 Using in vitro and in vivo models, we showed that a strong angiogenic response in temporal artery samples and strong angiogenic activity in serum are associated with a reduced prevalence of ischemic complications in patients with GCA, supporting the concept that the angiogenic response has a significant compensatory role in this disease. The angiogenic response in temporal arteries may not be functionally relevant in compensating for ischemia, but neovascularization may be crucial at distal sites in target organs.…”
Section: Discussionmentioning
confidence: 64%
“…25 We have proposed that angiogenesis may play a dual role in vasculitis which, in this regard, is unique among chronic inflammatory disorders. [13][14][15][16][17][18] Neovessels are the main site where endothelial cell adhesion molecules for leukocytes are expressed in medium-sized and large vessel vasculitis such as HUVECs differentiate into capillary-like structures on Matrigel. At low (2%) human serum concentration, tubes are incomplete and not well interconnected (A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms range from 2 to 50 % of patients with circulating cryoglobulins [40] and the typical presentation is the triad of purpura, arthralgia and weakness in roughly 80 % of symptomatic patients [12]; other manifestation of MC include sicca syndrome (10-25 %), neuropathy (11-30 %) and renal involvement such as membranoproliferative glomerulonephritis (20-25 %) [2,14,29,30]. The main therapeutic approach for MC in HCV patients is to eradicate the infection with standard treatment based on pegylated-interferon (PEG-IFN) and ribavirin (RBV) [32]; vasculitis exacerbation can occur during PEG-IFN administration [5,15], while treatment of symptoms with cytotoxic drugs or steroids should be reserved for limited cases due to difficulty of long-term management [4,19,28,41].…”
Section: Introductionmentioning
confidence: 99%
“…Teilweise ist sogar eine Verschlechterung der vorbestehenden Niereninsuffizienz oder Neuropathie sowie die verzögerte Abheilung offener Hautläsionen während einer IFN-Behandlung beschrieben. Ursächlich hierfür wird eine antiangiogenetische Wirkung des IFN vermutet [9].…”
Section: Gemischte Kryoglobulinämie Typ II Und Iiiunclassified